A clinical case of using therapeutic plasma exchange for the treatment of recurrent focal segmental glomerulosclerosis in a child after kidney transplantation - I. A. Miloserdov; V. S. Bogdanov; P. M. Gadzhieva; D. A. Saydulaev; A. A. Kartashev; E. G. Kulikova; I. E. Pashkova (Вестник трансплантологии и искусственных органов, 2021)
Background. Focal segmental glomerulosclerosis (FSGS) of the graft in kidney recipients is a rare and difficultto-diagnose post-kidney transplant complication, which can lead to graft loss and death of the recipient. A unified protocol is required for the treatment of this disease.Materials and methods. A 15-year-old female patient C. diagnosed with stage 5 chronic kidney disease as a result of steroid-resistant nephrotic syndrome with hematuria underwent a living related-donor kidney transplantation. On the third day after the operation, laboratory and imaging data showed kidney graft dysfunction. Patient examinations established the cause of the graft dysfunction – idiopathic nephrotic syndrome in FSGS.Results. For the treatment of recurrent FSGS, the patient had her immunosuppressive therapy converted from tacrolimus to cyclosporin A, and received two 500 mg rituximab injections. Ten sessions of therapeutic plasma exchange (Plasauto Sigma) were performed to remove antibodies to podocytes. During the therapy, diuresis was restored, creatinine and urea levels decreased. Six months after the kidney transplant, graft function was fully restored. Conclusion. The absence of recurrent FSGS within six months during a single course of therapeutic plasma exchange with its subsequent cancellation after restoration of graft function allows to recommend the developed method for the treatment of FSGS in pediatric patients after kidney transplantation.